Functionally graded adhesive joints – A review and prospects. (July 2017) - Durodola, J.F.
Abstract: There is increasing demand for effective and efficient lightweight structures because of global environmental and resource sustainability concerns. Adhesive bonding has been adopted in many assembly arrangements because of its relative reduction of stress concentration in joints compared to mechanical fasteners. Functionally graded bonded joints presents even greater potentials for reduction of stress concentrations and the tailoring of stress distribution as may be desired in an adhesive layer. This capability provides opportunity for the design of high performance tailored structural assemblies. Although some encouraging analysis and experimental work have been carried out on the development of functionally graded joints, its wide application is still to be realised. This paper reviews the work that has been carried out so far on the method, in terms of analysis, fabrication, experimental testing and application. It also reflects on outstanding issues that need to be resolved in order for wider application to be feasible.